The Effect of Prior Experience and Trust on Customer Loyalty with Satisfaction as an Intervening Variable - Maya Citra (PT Inovasi Pratama Internasional, 2022)
This study aims to find out how the Effect of Prior Experience and Trust on Customer Loyalty with Satisfaction as an Intervening Variable (Case Study on PT. High Cliff City Branch Pawnshop). The population in this study is all CUSTOMERS of PT. High Cliff Branch Pawnshop. In determining the sample, the slovin formula was used with the purposive sampling technique, the sample taken was 91 respondents. The analysis tool in this study was data processing using the help of IBM SPSS 25.0 0 for windows. The results of hypothesis testing use the t test (Partial) and to test the intervening variables of researchers using the path analysis method. From this test it can be concluded that based on the results of the analysis of hypothesis 1 it can be seen that t count ( 3.584 ) > t table ( 1.662 ), similarly with the significance value of 0.001 < 0.05 then it can be concluded that the first hypothesis of dit Erima, meaning that the Prior Experience Variable (X1) has an effect on the Satisfaction Variable (Z), hypothesis 2 can be known that t count ( 22.258 ) > t table ( 1.662 ), and the significance value is 0.000 < 0.05 then it can be concluded that the second hypothesis is accepted.